Improvement of in vitro shoot regeneration and flowering from petal explants of Begonia X hiemalis fotsch - Luan, Vu Quoc; Nhut, Duong Tan (Vietnam Journal of Biotechnology, 2024)
Begonias hold significant importance due to their use as culinary plants, medicinal remedies, decorative elements, and high-value crops. This research aims to find new explant materials for regeneration shoots and direct flowering with high frequency. In this study, high-frequency shoot regeneration and in vitro flowering from petal explants of Begonia x hiemalis Fotsch were achieved. Whole petal explants disinfected with an AgNPs solution at 0.5 g/L for 15 min achieved the highest survival rate. The highest shoot regeneration rate reached 86.66%, with 65.33 shoots/explant from ½-petal explants. Direct formation of the flower consists of two different structural forms, including single petal clusters and complete flower buds, with the corresponding flower formation rates of 19.66 petals/explant; 0.53 flower buds/explant, respectively, at the keel of the petals on the MS medium supplemented with 1000 mg/L myo-inositol, 1.0 mg/L BA, 1.0 mg/L NAA, 30 g/L sucrose and 9.0 g/L agar. Interestingly, increasing the concentration of myo-inositol in the culture medium led to the appearance of red-leaf shoots at the highest rate (12.66 shoots/explant), reaching a maximum shoot height of 1.40 cm after 8 weeks of culture. After each subculture, the red color on leaves tended to decrease gradually, and they were in vitro flowered after the second subculture at a rate of 15% and the third subculture at a rate of 10% on medium supplemented with 40 mg/L adenine, 1.0 mg/L NAA, 1.0 mg/L BA, 30 g/L sucrose, 9 g/L agar and 1 g/L activated charcoal. The plantlets regenerated from petal cultures bloomed with standard red pigments, similar to those grown in natural growing conditions.